Paikem's Approach to See Student Responses on Food Biotechnology Materials at SMP Negeri 3 Bambel - Muhammad Yassir; Habibul Akram (Journal of Business, Social and Technology, 2022)
This study aims to determine students' responses to the PAIKEM approach to food biotechnology material. The population in this study was all grade IX students of Bambel 3 Public Junior High School, Aceh Tenggaran Regency, for the 2021/2022 academic year, totalling 69 students. The sample taken in this study was one class from class IX-C with a total of 20 students. In class IX-C, qualitative research methods were carried out using a descriptive design and purposive sampling technique. The results of students' responses regarding the PAIKEM approach of class IX students on food biotechnology material at Bambel 3 Public Junior High School were 0.80. According to the inter-achievement guidelines, the interval coefficient at a score of 0.80-1.00 was very high.